Association of sedentary behaviours with food and beverages consumption and total diet quality in children from a Spanish region. The Calina study. Issue 1 (1st January 2020) - Miguel-Berges, María L; Flores Barrantes, Paloma; Iglesia Altaba, Iris; Santaliestra-Pasias, Alba; Samper, Pilar; A. Moreno, Luis; Rodriguez, Gerardo
ABSTRACT: Introduction: The time spent in different types of sedentary behaviours has been associated with a poor intake in children, which contributes to childhood obesity. The aims of this study were: to examine the association between sedentary behaviours and the adherence to the total screen time (TST) recommendations, food and beverage consumption and the total diet quality index (DQI), in a sample of Spanish children. Methods: The study included a cohort of 420 children (53.6% boys) aged 7 years from Zaragoza (Spain), belonging the Growth and Feeding during Infancy and Early Childhood in Aragon (CALINA) longitudinal study. Data on dietary habits and TST (watching TV/DVD/videos and playing/using personal computers (PC)/video games) were parental-reported. TST was categorized based on the recommendations (≤2 h/day and >2 h/day). The DQI was computed from a validated semi-quantitative food-frequency questionnaire. Generalized linear mixed models, adjusted by maternal education, ethnicity and body mass index of the children, were analysed. Results: Both in boys and girls, using a PC for ≤2 h per day was associated with a lower consumption of sugar and artificially sweetened beverages. In boys, using PC for ≤2 h per day was associated with a lower consumption of sweets, desserts and salty snacks and in girls, were associated with a lower consumption of juices and a higher consumption of fruits and vegetables. Only in boys, a low TST per day was assSociated with a lower consumption of sugar-sweetened beverages, whereas in girls, it was associated with a lower consumption of artificially sweetened beverages. Regarding DQI, both, boys and girls, showed inverse associations between watching TV and total ST and the DQI; boys and girls meeting the TST recommendations (<2 h/day) had a better diet quality. Discussion: Sedentary behaviours were associated with unhealthy food and beverage consumption and a low total diet quality.